B lymphocytes from patients with chronic lymphocytic leukemia contain signal transducer and activator of transcription (STAT) 1 and STAT3 constitutively phosphorylated on serine residues. - Frank, D A (1997)
To explore the pathogenesis of chronic lymphocytic leukemia (CLL), we examined whether phosphorylation of one or more signal transducer and activator of transcription (STAT) factors was abnormal in cells from CLL patients. No constitutive tyrosine phosphorylation was detected on any STAT in CLL cells. To assess the phosphorylation of serine residues of STAT1 and STAT3 in CLL cells, we raised antibodies that specifically recognize the form of STAT1 phosphorylated on ser-727 and the form of STAT3 phosphorylated on ser-727. We found that in 100% of patients with CLL (n = 32), STAT1 and STAT3 were constitutively phosphorylated on serine. This was in contrast to normal peripheral blood B lymphocytes or CD5+) B cells isolated from tonsils, in which this phosphorylation was absent. Serine phosphorylation of STAT1 and STAT3 was seen occasionally in other leukemias, but it was a universal finding only in CLL. The serine phosphorylation of these STATs was a continuous process, as incubation of CLL cells with the kinase inhibitor H7 led to the dephosphorylation of these serine residues. The STAT serine kinase in CLL cells has not been identified, and appears to be neither mitogen-activated protein kinase nor pp70(s6k). In summary, the constitutive serine phosphorylation of STAT1 and STAT3 is present in all CLL samples tested to date, although the physiologic significance of this modification remains to be determined.